Re-examining the effectiveness of monetary policy in achieving price stability and output growth in Botswana - Tlhako, Kefilwe (University of the Witwatersrand, Johannesburg, 2024)
This study reassessed the effectiveness of Botswana's monetary policy, emphasizing its two main goals of maintaining price stability and promoting output growth. Output and inflation are our dependent variables, and they are proxied, respectively by mining and non-mining GDP and the consumer price index. We examined quarterly data from 2005 to 2022 using a Vector Error Correction model. Stationarity tests were conducted using both the ADF test and the Phillips-perron (PP-test), where both tests confirmed all variables to be stationary at levels except money supply which was stationary at first differences. Through the integration of macroeconomic factors like inflation, GDP, interest rates, exchange rates, money supply, and the bank rate, our goal is to offer a thorough comprehension of the relationship between monetary policy decisions and their consequences in the economy of Botswana, a small open economy that is prone to both internal and external shocks. By considering both internal and external elements that could have an impact on the framework's performance, our analysis provides light on how less effective Botswana's monetary policy framework has been over the studied period. The results from the study show that policy shocks have little effect on output growth and inflation. This is proven by the results of the VECM showing a significant impact of the bank rate on non-mining GDP only, while the other two variables; mining GDP and inflation proved that the bank rate does not impact them both in the short run and long run. The VAR decomposition also showed that at most 5% of the changes in our dependent variables are explained by the shocks on the bank rate. The results bring us to the conclusion that other external shocks, such as controlled prices and exchange rates, are the primary causes of inflation than it is driven by the bank rate. With respect to output, the results bring us to the conclusion that the mining sector is heavily influenced by global commodity prices, which are determined by international supply and demand dynamics, rather than domestic interest rates. So significant changes in the bank rate may not alter these global factors. Lastly the non- mining GDP is seen to respond to changes in the bank rate due to the interest rate sensitivity of the sector. The non-mining sector is made up of sectors such as manufacturing, services, retail etc, and these are very sensitive to changes in the interest rates as they rely mainly on short term borrowings for capital and investment. Therefore, changes in the bank rate quickly affect lending rates, consumer loans and business financing, leasing to more immediate economic impacts. Based on the above results, we therefore recommend that policy makers should diversify monetary policy tools and implement sector specific support for the mining industry and focus more on controlling external factors such as exchange rates. 4 Enhanced financial sector regulation and coordination with fiscal policy are also crucial. The employment of these measures can help stabilize the economy and improve the effectiveness of monetary policy, and ensure that non-mining sectors which are more sensitive to interest rates changes, benefit from targeted interventions. This holistic approach acknowledges the varying responsiveness of different sectors and the influence of global economic conditions.
A research report submitted in fulfillment of the requirements for the Master of Commerce (Economics), In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Botswana's monetary policy; SDG-8: Decent work and economic growth